2014
DOI: 10.1007/s12032-014-0944-1
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine-based therapy as first-line treatment for non-Hodgkin lymphoma

Abstract: Recently, bendamustine has become an important agent in the treatment for patients with lymphoid malignancies. Although the drug has received approval for second-line therapy in indolent lymphoma, a growing body of evidence suggests its efficacy and safety in first-line use. The results of randomised and observational studies with bendamustine as front-line therapy in non-Hodgkin lymphoma (NHL) with emphasis on efficacy and toxicity are presented. Furthermore, completed and ongoing clinical trials evaluating u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…However, the management of relapsed/refractory disease represents a challenge, and a series of novel agents have entered clinical trials. Among these new strategies, bendamustine (Ben), a bifunctional alkylating agent, in combination with rituximab could be recommended as a first-line therapy for MCL (34). In our study, we first observed the cytotoxic effect and apoptosis induced by R and/or Ben in Maver and Z138 cells, and the results confirmed that silencing of B7-H3 increases chemosensitivity in both the single drug and two drug combination groups.…”
Section: Discussionsupporting
confidence: 70%
“…However, the management of relapsed/refractory disease represents a challenge, and a series of novel agents have entered clinical trials. Among these new strategies, bendamustine (Ben), a bifunctional alkylating agent, in combination with rituximab could be recommended as a first-line therapy for MCL (34). In our study, we first observed the cytotoxic effect and apoptosis induced by R and/or Ben in Maver and Z138 cells, and the results confirmed that silencing of B7-H3 increases chemosensitivity in both the single drug and two drug combination groups.…”
Section: Discussionsupporting
confidence: 70%
“… 80 BR regimen has gained popularity in the US for excellent tolerance and superior outcomes in other indolent B-cell lymphomas. 105 ORR of 93% has been achieved in patients with R/R EMZL (CR 71%) with the BR regimen with durable remissions at a cost of 29% incidence of Grade III–IV hematological toxicity. 106 The proteasome inhibitor bortezomib also has significant single-agent activity in R/R EMZL with an ORR of 48% (CR 31%).…”
Section: Management Of Mzlmentioning
confidence: 99%
“…In the 1990s bendamustine got into the focus of research again [ 6 ]. It is approved for the treatment of chronic lymphocytic leukemia (CLL) [ 7 , 8 ], indolent non-Hodgkin lymphoma (NHL) [ 9 ] and multiple myeloma (MM) [ 10 , 11 ] or as second line therapy of refractory diseases [ 12 14 ] in various countries. Current clinical trials suggest beneficial effects in the treatment of solid cancer types such as breast cancer [ 15 ] or small-cell lung cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%